2017
DOI: 10.1007/s10482-017-0953-0
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum WhcD interacts with WhiA to exert a regulatory effect on cell division genes

Abstract: Corynebacterium glutamicum WhcD plays an important regulatory role in cell division. Binding of WhcD to the promoter region of its target genes, such as ftsZ, was observed by electrophoretic mobility shift assays (EMSA) using purified fusion proteins; however, binding could only be observed in the presence of WhiA. Although WhcD alone did not bind to the DNA, it stimulated binding of WhiA to the promoter region of the cell division gene ftsZ. Binding of WhcD and WhiA to DNA did not occur in the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Despite the fact that WhiA is conserved in Gram-positive bacteria and is required for optimal growth in B. subtilis, surprisingly little is known about its mechanistic role. The only other organisms in which the function of WhiA has been studied are streptomycetes and C. glutamicum, and in these organisms, the protein functions as a transcription factor (4,5,19). In B. subtilis, WhiA also binds DNA, but the protein does not bind specifically to promoter regions and does not seem to function as a transcription factor in this organism (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that WhiA is conserved in Gram-positive bacteria and is required for optimal growth in B. subtilis, surprisingly little is known about its mechanistic role. The only other organisms in which the function of WhiA has been studied are streptomycetes and C. glutamicum, and in these organisms, the protein functions as a transcription factor (4,5,19). In B. subtilis, WhiA also binds DNA, but the protein does not bind specifically to promoter regions and does not seem to function as a transcription factor in this organism (7).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in whiA prevent the induction of FtsZ and block sporulation (1)(2)(3)(4). WhiA binds DNA and functions as a transcription activator of ftsZ and other differentiation genes in Streptomyces spp., and recently, it has been shown to regulate ftsZ in Corynebacterium glutamicum as well (4,5).…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…In Corynebacterium, the orthologue of WhiB, WhcD Cg , similarly regulates the transcription of genes required for cell division and directly interacts with the orthologue of WhiA in vitro (Lee et al , ; ) . WhcD Cg cannot bind to promoter DNA by itself but stimulates the binding of WhiA to the ftsZ promoter, suggesting that WhcD enhances the DNA‐binding activity of WhiA through protein–protein interaction (Lee et al , ).…”
Section: Class II (Whib2/whib/whcd)mentioning
confidence: 99%
“…The interaction of Wbl proteins with other proteins is also known; work in both Streptomyces and Corynebacterium revealed that WhiB controls the process of sporulation via a direct interaction with a (non-Wbl) transcription factor called WhiA (5,16). Thus, evidence is accumulating that Wbl proteins function together with partner proteins.…”
mentioning
confidence: 99%